2021
DOI: 10.2478/izajole-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recreational cannabis access on labor markets: evidence from Colorado

Abstract: Recreational cannabis markets possibly increase labor demand through investments in facilities for growing, processing, and retail sales of cannabis, as well as through other industries such as manufacturing, leisure, and hospitality. However, this increase in labor demand may vary substantially across counties within a state as most states with legal recreational cannabis allow individual counties to ban commercial cannabis sales. Meanwhile, labor supply may change through positive and negative effects from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Dragone et al (2019) found that recreational marijuana legalization in Washington is associated with a reduction of rape and thefts, while the opening of retail cannabis stores in Denver is associated with an increase in property crimes (Connealy et al, 2020). On the labor market, the creation of the newly legal cannabis industry can increase labor demand, reducing unemployment (Chakraborty et al, 2021). My analysis contributes to these studies by examining the potential effects of recreational marijuana dispensaries on traffic crashes, which is one of the main concerns of expanding access to marijuana.…”
Section: Introductionmentioning
confidence: 99%
“…Dragone et al (2019) found that recreational marijuana legalization in Washington is associated with a reduction of rape and thefts, while the opening of retail cannabis stores in Denver is associated with an increase in property crimes (Connealy et al, 2020). On the labor market, the creation of the newly legal cannabis industry can increase labor demand, reducing unemployment (Chakraborty et al, 2021). My analysis contributes to these studies by examining the potential effects of recreational marijuana dispensaries on traffic crashes, which is one of the main concerns of expanding access to marijuana.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies examine the impact of recreational marijuana access on labor market and social insurance outcomes. First, Chakraborty et al (2021) show that the opening of dispensaries in Colorado reduces unemployment rates but has minimal effects on labor market participation or wages. Second, Dong (2020) finds that workplace injuries in Oregon increase after a county legalizes the sale of recreational marijuana.…”
Section: Background On Marijuana Legalization Lawsmentioning
confidence: 99%
“…RMLs may also offer a boost to the economy (Chakraborty et al, 2021;Dave et al, 2023). Improved labor market opportunities could increase WC receipt as there are more employed individuals at risk of a work-related injury.…”
Section: Mechanisms For a Relationship Between Rmls And Workers' Comp...mentioning
confidence: 99%
See 2 more Smart Citations